Build Android-Based Go Service Electronic Applications Using React Native Framework and Firebase Realtime Database - Aulia, Rahmad; Suendri; Alda, Muhamad (Ali Institute or Research and Publication, 2023)
Many entrepreneurs provide electronic services, especially on cellphones and PCs, but their marketing is very limited due to the location of the store and banners that are not strategic so it is difficult to know where the service is located, on the other hand customers are also difficult to know the estimated cost of repairing electronic devices and often potential customers I was disappointed when I arrived at the location but the service was closed. With these problems, the author built an Android-based Go Service Electronic application by utilizing React Native Framework technology to build Android-based applications and using the Firebase Realtime Database as data storage. The application is also equipped with consulting features, a booking system, calculating the estimated cost of equipment repair services, as well as providing information on the best service services through an assessment system that has been provided by customers who have booked previous services. With the Go Service Electronic application, it is easier for the public to find out where the location of service providers is, find out the estimated repair costs, and can consult directly through the application, as well as being able to increase business opportunities for electronic service providers.